2018
DOI: 10.1002/ajp.22915
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal oxytocin in rhesus monkeys alters brain networks that detect social salience and reward

Abstract: In primates, resting state functional neuroimaging (rsfcMRI) has identified several large-scale, intrinsic brain networks, including the salience network (SN), which is involved in detecting stimulus salience. Intranasal oxytocin (IN-OT) has been shown to modulate the salience and rewarding quality of social stimuli in mammals and numerous studies have shown that it can affect the functional connectivity between brain regions. Less is known, however, about how these effects unfold over time following IN-OT adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Although more research is needed to determine whether facial identity and expression are processed by independent neural mechanisms 3840 , our results indicate that intranasal OT selectively alters the sensitivity of monkeys to facial expressions, possibly via an interaction with motivation and reward circuitry in the primate brain (i.e. the amygdala) 34,48,49 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Although more research is needed to determine whether facial identity and expression are processed by independent neural mechanisms 3840 , our results indicate that intranasal OT selectively alters the sensitivity of monkeys to facial expressions, possibly via an interaction with motivation and reward circuitry in the primate brain (i.e. the amygdala) 34,48,49 .…”
Section: Discussionmentioning
confidence: 84%
“…This indicates that the amygdala is involved at an early stage of information processing, when orienting and directing one’s eye movements towards salient environmental stimuli and those with emotional valence. Since a previous functional imaging study found that the response to facial expressions with negative valence in the monkey amygdala was selectively reduced by the delivery of OT 44,45 , it may be that our results from the OT treatment condition reflect a change in the subject’s viewing behavior stemming from altered amygdala activity 20,29,34,46 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, the medial prefrontal activity in response to ingroup pain in the revenge group, but not in the control group mediates the association between endogenous oxytocin and the propensity to give painful electrical shocks to outgroup members, regardless of whether or not they were personally involved in the conflict [52]. Oxytocin also modulate rodent and monkeys' performance in memory tasks, and both increased and reduced effects were reported [53][54][55][56][57]. The effects of oxytocin on the perception and evaluation of social stimuli greatly was dependent on the emotional/social valence of stimuli [58] and it is suggested that oxytocin's effect is context-dependently in monkeys [58,59].…”
Section: Selective Hypothesismentioning
confidence: 99%
“…Endogenous hormone and neuropeptide levels are important for biobehavioral feedback and to help animals respond appropriately to various social interactions. Oxytocin (OXT), a neuropeptide hormone, is a neuromodulator that may be important for weighing social salience and determining appropriate behavioral response to social stimuli (Shamay-Tsoory & Abu-Akel, 2016; Parr et al, 2018; Yao et al, 2018; Johnson et al, 2017; Egito et al, 2020). Previous studies on OXT show its significant effects on prosocial affiliative behaviors such as trust, social bonding, social recognition, and anxiolytic behavior in both human and animal models (Theodoridou et al, 2009; Kosfeld et al, 2005; Ring et al, 2006; Bales et al, 2003; Blocker et al, 2015; Guestella et al, 2008).…”
Section: Introductionmentioning
confidence: 99%